2009
DOI: 10.1007/s00246-009-9514-2
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal Anomalies Influence Parental Treatment Decisions in Relation to Prenatally Diagnosed Congenital Heart Disease

Abstract: This study aimed to identify the variables that influence parental treatment decisions after a prenatal diagnosis of congenital heart disease (CHD). The authors reviewed all cases of prenatally diagnosed structural CHD from August 1998 to December 2006 at their center. The following variables were studied as potential predictors of parental intent to treat: maternal age, race, insurance status, obstetric history, fetal gender, univentricular versus biventricular cardiac physiology, and fetal chromosomal abnorm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 20 publications
3
29
0
Order By: Relevance
“…We also showed that these associations were independent of the severity of the CHD, represented by defects unsuitable for biventricular repair. Our results were consistent with those of previous studies [15,17,19,20]. Russo et al showed that termination of pregnancy was [19].…”
Section: Discussionsupporting
confidence: 95%
See 2 more Smart Citations
“…We also showed that these associations were independent of the severity of the CHD, represented by defects unsuitable for biventricular repair. Our results were consistent with those of previous studies [15,17,19,20]. Russo et al showed that termination of pregnancy was [19].…”
Section: Discussionsupporting
confidence: 95%
“…Several other pregnancy variables are known to influence the decision to terminate pregnancy, such as maternal age, gravida, parity, gestational age at time of diagnosis, religion and socioeconomic status [16,17,21]. Furthermore, survival rate can be influenced by many other factors [22][23][24], such as term of birth or birth weight.…”
Section: Study Limitationsmentioning
confidence: 97%
See 1 more Smart Citation
“…Timely identification of genetic/ chromosomal abnormalities may strongly influence decisions concerning termination of pregnancy. 411 Amniocentesis and additional imaging (eg, high-level obstetric ultrasound, fetal MRI) can contribute to a more complete characterization of the fetus and may be offered to the family. Such testing may aid in making decisions about the continuation of the pregnancy or in planning for specific needs at birth for care beyond the heart.…”
Section: Techniquesmentioning
confidence: 99%
“…The parental decision following the diagnosis varies between countries and even between different medical centers in the same country [10,13,14,15]. Factors that can influence this decision of continuing or terminating a pregnancy include the specific cardiac and extracardiac anomaly and its prognosis [7,16,17,18,19].…”
Section: Introductionmentioning
confidence: 99%